The Mpox Threat: Challenges and Implications of Clade Ib for Afghanistan’s Healthcare Stability - Bek B; Fayaz Y; Bek R; Ahmadi SU (Dove Medical Press, 2024)
Basira Bek,1 Yahya Fayaz,2 Rahila Bek,1 Shahab Uddin Ahmadi2 1Department of Medicine, Kateb University, Kabul, Afghanistan; 2Department of Stomatology, Khatam AL Nabieen University, Kabul, AfghanistanCorrespondence: Yahya Fayaz, Department of Stomatology, Khatam AL Nabieen University, Kabul, Afghanistan, Tel +93 (0) 706281798, Email dr.yahyafayaz@gmail.comAbstract: The global spread of the Mpox virus represents a significant public health challenge, particularly for regions with fragile healthcare systems. Afghanistan, already grappling with severe healthcare deficits, faces the added threat of Mpox, a zoonotic disease caused by the monkeypox virus. The recent emergence of Clade Ib, a new strain associated with rising outbreak cases, exacerbates concerns as Afghanistan's healthcare infrastructure continues to deteriorate due to reduced international aid, healthcare worker shortages, and an ongoing socio-political crisis. This commentary underscores the urgent need for international intervention to avert a potential public health crisis that could devastate Afghanistan's already weakened healthcare system. It calls for immediate support to enhance disease surveillance, improve healthcare infrastructure, and address the pressing challenges of malnutrition and access to medical services.Keywords: monkeypox virus, outbreak, Afghanistan